2004
DOI: 10.1097/01.mlr.0000132392.49176.5a
|View full text |Cite
|
Sign up to set email alerts
|

Improving Identification of Hispanic Males in Medicare

Abstract: Augmenting the Medicare race code with a match to Spanish surnames yields substantial improvement in the identification of elderly Hispanic and white non-Hispanic male Medicare beneficiaries. Using surname information to supplement the Medicare race code could greatly enhance researchers' ability to examine healthcare equity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 6 publications
2
32
0
1
Order By: Relevance
“…Perkins (1993) suggests that a Spanish surname match is less efficient in areas with low concentrations of Hispanics. However, in this study we found consistent improvement of accuracy in identifying Hispanics using the combined Medicare race code and Spanish surname indicator across areas that vary widely in the concentration of Hispanics for both men and women (Figures 1 and 2), as also shown previously among men (Morgan, Wei, and Virnig 2004). Nevertheless, it is undetermined if our results can be generalized to areas outside of our sampling frame, particularly those areas with extremely low concentrations of Hispanics.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…Perkins (1993) suggests that a Spanish surname match is less efficient in areas with low concentrations of Hispanics. However, in this study we found consistent improvement of accuracy in identifying Hispanics using the combined Medicare race code and Spanish surname indicator across areas that vary widely in the concentration of Hispanics for both men and women (Figures 1 and 2), as also shown previously among men (Morgan, Wei, and Virnig 2004). Nevertheless, it is undetermined if our results can be generalized to areas outside of our sampling frame, particularly those areas with extremely low concentrations of Hispanics.…”
Section: Discussionmentioning
confidence: 42%
“…Further, Hispanics often choose to identify with a country of personal or ancestral origin rather than the general classification of ''Hispanic.'' For example, in our studies, when Hispanics have chosen a response of ''other'' for their race/ethnicity, it has not been unusual for them to write in a designation such as ''Venezuelan'' or ''white Cuban American'' (Morgan, Wei, and Virnig 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Generally Useful Ethnic Search System, or GUESS, is a previously validated surname program for identifying Hispanic subpopulations in the southwest [8][9][10][11][12]. The GUESS program was revised and validated using state tumor registry records by the Lovelace Clinic Foundation in Albuquerque, New Mexico [6].…”
Section: Introductionmentioning
confidence: 99%